'Nominális', reálgazdasági és árszintfelzárkózás az Európai Unióban 1995 és 2019 között - Oblath Gábor (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
– Significant cross-country differences in real income levels are accompanied by sizable differences in price levels, and, in the longer run, convergence in real income levels goes together with convergence in price levels. Although the cross-country comparison of nominal per capita GDP levels at current exchange rates is neither suitable to measure real income differences, nor their changes over time, their decomposition into a 'real' and price component can reveal the contribution of the two factors to 'nominal convergence'. The decomposition may be performed by drawing on two statistical sources, providing conflicting indications with respect to relative price and real changes in the case of several member states of the European Union. However, both statistics suggest that the rapid 'nominal convergence' of the Central and East European member-states between 1995 and 2008 mainly stemmed from the swift convergence in price levels (real exchange rate appreciation), while the deadlock in nominal convergence after 2009 is mainly due to the halt (reversal) in price convergence. Real economic convergence of the CEEU-region continued in the 2010s, albeit at a slower pace.
Keywords: E01; F43; O47; O52; 330; comparative price and income levels; economic convergence; national accounts; purchasing power parities; European Union